Quality improvement project to reduce length of stay for patients with urinary tract infections in an NHS hospital trust - Molly Crawford (BMJ Open Quality)
The bed day reduction improvement project for patients with urinary tract infections was commissioned at Frimley Health NHS Foundation Trust as inpatient length of stay (LOS) has been increasing over time, with noticeable variance between conditions and treatment pathways.A multidisciplinary group was formed with staff from infection control, urology and medicine. A3 thinking (a quality improvement method) was used to define the problem, analyse the data, complete root cause analysis and test change. The project aimed to impact the whole hospital system; however, using quality improvement methodology, the area with the biggest potential impact was focused on which was the emergency department. This is because positive changes made at the front end cause better outcomes throughout the pathway. Change ideas included reducing urine sample errors by improving labelling, increasing the number sent off by making the sample collection process easier for staff, increasing the use of Same Day Emergency Care Unit (SDEC) to avoid unnecessary admissions by raising awareness of the pathway with doctors and designing a pathway direct from triage to SDEC.A link was demonstrated, through audit, between sample errors/not sent and prolonged LOS, confirming the opportunity of reducing sample errors. White-topped urine sample errors reduced by 50% following the process change. The work done to reduce errors has led to an approximate 10 days per month bed day saving, improving patient experience, care and staff morale. There was no significant increase in urine samples sent, the urology SDEC use increased marginally and the triage pathway was implemented. The project was unable to link the individual changes to a reduction in the outcome measure of bed days.